ANALISIS KELAYAKAN USAHA JAMUR TIRAM (Pleurotus ostreatus) DENGAN INOVASI PENGOLAHAN HASIL PRODUK MENJADI JAMUR CRISPY: STUDI KASUS PELAKU USAHA JAMUR TIRAM DI DESA KEMIRI KECAMATAN MOJOSONGO KABUPATEN BOYOLALI - Etty Sri Hertini (Undana Press, 2021)
This study aims to determine the feasibility of oyster mushroom cultivation with the innovation of crispy mushroom processed products. This research is a qualitative descriptive research with a case study approach. Data analysis in this study used descriptive qualitative analysis. Data collection in this study used interview techniques with 16 fresh oyster mushroom business actors in Kemiri Village, Mojosongo District, Boyolali Regency during the production period from November 2020 to February 2021, both of which were sold in the form of fresh mushrooms and in the form of processed crispy mushroom products. Determination of the location and informants in this study using a purposive method. The results of this study indicate that the oyster mushroom cultivation business, whether sold in the form of fresh mushrooms or in the form of processed products of crispy mushrooms, has the potential to be quite profitable, because the business has more than one efficiency value. Furthermore, the innovation of processing fresh mushroom products into crispy mushrooms has the potential to increase income for oyster mushroom business actors, because the analysis of this study shows a fairly good level of efficiency. However, increasing the quality of crispy mushroom processed products needs attention so that these products can be sold at higher prices, so that the benefits derived from product processing innovations are also more attractive.